2001
DOI: 10.1128/iai.69.9.5589-5596.2001
|View full text |Cite
|
Sign up to set email alerts
|

Laccase of Cryptococcus neoformans Is a Cell Wall-Associated Virulence Factor

Abstract: Virulence is the outcome of an interaction between the host and a microbe and is characterized by a large array of opposing reactions operating at the host-pathogen interface. Cryptococcus neoformans is an important opportunistic pathogen in immunocompromised patients, including those with human immunodeficiency virus, and expresses a virulence-associated laccase which is believed to oxidize brain catecholamines and iron as a defense against host immune cells. In the present report, we investigated the cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(145 citation statements)
references
References 41 publications
5
138
0
2
Order By: Relevance
“…Previous studies suggested that melanization occurred when laccase in the cell wall oxidized a substrate, such as L-DOPA, ultimately resulting in polymerization of melanin (Waterman et al, 2007;Zhu et al, 2001). However, recent studies showing the presence of cell-wall-associated vesicles exhibiting laccase activity raised the possibility of the involvement of vesicles in melanization (Rodrigues et al, 2008).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous studies suggested that melanization occurred when laccase in the cell wall oxidized a substrate, such as L-DOPA, ultimately resulting in polymerization of melanin (Waterman et al, 2007;Zhu et al, 2001). However, recent studies showing the presence of cell-wall-associated vesicles exhibiting laccase activity raised the possibility of the involvement of vesicles in melanization (Rodrigues et al, 2008).…”
Section: Discussionmentioning
confidence: 82%
“…Melanization of C. neoformans depends on the presence of substrate, such as L-3,4-dihydroxyphenylalanine (L-DOPA) and other catecholamines (Garcia-Rivera et al, 2005). In addition, it requires expression of laccase, a cell wall enzyme that is associated with virulence (Zhu et al, 2001). In melanized cells, melanin is found in the cell wall of the yeast .…”
Section: Introductionmentioning
confidence: 99%
“…B. subtilis endospore coat protein shows CotA oxidase activity with all the structural features of laccase, including the reactive surface exposed copper center T1 and two buried copper centers (T2 and T3) [29]. Cot A is naturally associated with the coat structure in active form, which suggests B. subtilis endospore coat structure as a surface display system for biocatalyst applications involving the stable CotA laccase [38]. Comparison of B. subtilis CotA with other multicopper oxidases shows that copper binding motives are conserved in all sequences.…”
Section: Laccase Shows Cota Oxidase Activitymentioning
confidence: 99%
“…Recombinant cryptococcal laccase exhibits iron oxidase activity by converting Fe (II) to Fe (III) [27]. Moreover, laccase from C. neoformans is implicated in the virulence of the organism by virtue of its oxidizing action on the brain catecholamines as a defense system against host immune system [2,29]. Its differential function when secreted by different type of cells adds it to the moonlighting list (Fig.…”
Section: Reactions Catalyzed By Laccasesmentioning
confidence: 99%
See 1 more Smart Citation